Trichobilharzia regenti (Digenea: Schistosomatidae): changes of body wall musculature during the development from miracidium to adult worm - Bulantová, Jana; Chanová, Marta; Houžvičková, Lenka; Horák, Petr (Micron (Oxford, England, 2011)
Trichobilharzia regenti (Schistosomatidae, Digenea), a parasite of birds, exhibits a unique strategy among schistosomes, having affinity to the nervous system of vertebrate hosts. Migration of parasitic stages within hosts and/or swimming of non-parasitic larvae in water environment depend on the action of body wall muscles which were studied with confocal and electron microscopy. In all stages, body wall musculature is comprised of differently organized circular and longitudinal muscles. During the development, an extensive change of musculature characteristics and/or formation of new muscle structures were recorded; cercariae, schistosomula and adult worms produce additional underlying diagonal muscle fibers and inner plexus of radial musculature. Substantial changes of the outer environment during penetration of a host (osmotic values of water vs. host tissues) are accompanied by surface transformation of miracidia/mother sporocysts and cercariae/schistosomula. Contrary to that, changes of body musculature in these stages are characterized only by growth and re-organization of existing structures, and never by formation of new components of body musculature. Future studies in this field may contribute to a better knowledge of morphology and function of trematode muscles, including those of schistosomes that are important pathogens of humans and animals.
Keywords: elektronová mikroskopie; Microscopy, Confocal; ptáci; Birds; Schistosomatidae; Animals; Musculoskeletal Development; muskuloskeletální vývoj; zvířata; konfokální mikroskopie; Microscopy, Electron